2019
DOI: 10.30773/pi.2019.0063
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between 10 Years Risk of Cardiovascular Disease and Schizophrenia Symptoms: Preliminary Results

Abstract: ObjectivePrevious research shows that patients with schizophrenia have increased cardiovascular disease risk than general population. Increased cardiovascular risk in schizophrenia patients have been associated with many reasons such as antipsychotic drugs, genetic predisposition, andlifestyle. In this study, we aimed to investigate the relationship between the risk of heart disease and schizophrenia symptomatology. MethodsThe 10-year cardiovascular risk was assessed by the Framingham Risk Score (FRS) in 103 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
0
6
0
1
Order By: Relevance
“…Serupa dengan Bär, (2015) bahwa mayoritas kematian terbanyak di antara pasien skizofrenia disebabkan oleh komplikasi kardiovaskuler, khususnya penyakit jantung koroner. Selain itu, hasil penelitian Kilicaslan, et al, (2019) juga menunjukkan bahwa faktor lingkungan dan juga genetik merupakan etiologi dari penyakit kardiovaskular yang dapat memperpendek harapan hidup pasien skizofrenia.…”
Section: Pembahasanunclassified
“…Serupa dengan Bär, (2015) bahwa mayoritas kematian terbanyak di antara pasien skizofrenia disebabkan oleh komplikasi kardiovaskuler, khususnya penyakit jantung koroner. Selain itu, hasil penelitian Kilicaslan, et al, (2019) juga menunjukkan bahwa faktor lingkungan dan juga genetik merupakan etiologi dari penyakit kardiovaskular yang dapat memperpendek harapan hidup pasien skizofrenia.…”
Section: Pembahasanunclassified
“…Some studies that calculate CVD risk scores using algorithms have also reported that people diagnosed with SMI have increased CVD risk when compared to healthy controls. For example, Kilicaslan et al (2019) concluded that the 10-year cardiovascular risk of 103 Turkish inpatients with schizophrenia was significantly higher than 39 healthy matched controls (5.16% vs. 3.02%, p=0.03). Similarly, a Chinese study involving 466 inpatients with schizophrenia (Zhao et al, 2018) reported that their Framingham 10year CVD risk score was significantly higher than the 507 healthy controls (6.7% vs. 4.8%, p < 0.001).…”
Section: Cardiovascular Disease Risk In Severe Mental Illnessmentioning
confidence: 99%
“…Some studies that calculate CVD risk scores using algorithms have also reported that people diagnosed with SMI have increased CVD risk when compared to healthy controls. For example, Kilicaslan et al (2019) concluded that the 10-year CVD of 103 Turkish inpatients diagnosed with schizophrenia was significantly higher than 39 healthy matched controls (5.16% vs. 3.02%, p = .03).…”
Section: Cardiovascular Disease Risk In Severe Mental Illnessmentioning
confidence: 99%
“…For example, there is evidence of a positive association between antipsychotic polypharmacy, duration of exposure to antipsychotics and cardiovascular disease mortality (Ganguly et al, 2004; Weinmann et al, 2009). Likewise, a few studies have also demonstrated that elevated CVD risk score is associated with taking higher doses of antipsychotics (Bressington et al, 2016) and usage of multiple types of antipsychotics (Killiscan et al, 2019). However, these studies did not involve people with early‐stage psychosis.…”
Section: Introductionmentioning
confidence: 99%